Barriers to cataract surgery from the perspective of patients with cataract blindness in the Eastern zone of Peninsular Malaysia: an interpretative phenomenological analysis - Nurulain Mat Zin; Universiti Sultan Zainal Abidin . Faculty of Medicine (2017)
Cataract is the chief cause 0 f visual impairment worldwide and is the single most important cause of blindness affecting half of the blind global population. The National Eye Survey 2 (NES2) revealed cataract as the leading cause of blindness and visual impairment in the whole of Malaysia with the prevalence of 1.2 % and 5.4 % respectively. The total number of cataract backlog that require surgery for the whole country in 2014 was estimated to be more than six hundred thousand. Understanding the issues concerning the barriers to undertake early cataract surgery is warranted to effectively increase the cataract surgical rate and reduce the prevalence of cataract blindness. Thus, in this study we intend to explore the barriers to cataract surgery from the perspective of patients with cataract who have not gone for surgery even up to the point of blindness. Semi-structured interviews were carried out on eleven participants in the Eastern zone of Peninsular Malaysia who had been diagnosed with severe cataract blindness from the state of Kelantan, Terengganu and Pahang. The interviews were tape recorded and transcribed verbatim. Interpretative Phenomenological Analysis (lPA) approach was utilised in the coding process to identify and categorise the emerging themes. Our study identified barriers to cataract surgery at three levels i.e. at the patient's level, primary care level, and specialist care level. Barriers at the patient's level are issues pertaining to their perceived need for sight, worry, general physical status, amount of family support and cost incurred. Barrier at the primary care level is regarding refusal to disclose eye problem and pat icnt-provider related issues. The specialist care level are concerning healthcare system accessibility, bureaucracy, waiting time and cost of surgery. However, most of the subthemes identified are interrelated and may have significant contributions at every level of the barriers. Majority of the barriers are at the patient's level. Most of the participants emphasised their needs and capability to perform daily living activities in spite of their limited vision. Their perceived need for sight, thoughts, feeling and awareness contribute to their initial decision to disclose their visual problem to family members Of primary healthcare providers for alternative treatment or to undertake cataract surgery. Their lack of family support, difficulties in daily living expenditure and cost incurred are also major issues. However, appropriate approach and advice from healthcare providers may be able to influent patients for an earlier cataract surgery. Thus, further improvement in our health education, promotion, vision screening and eyecare delivery system will certainly increase the awareness of the community and healthcare provider about cataract.
1. Introduction -- 2. Literature review -- 3. Methodology -- 4. Results -- 5. Discussion
Thesis (Degree of Master, Medicine) - Universiti Sultan Zainal Abidin, 2017
Includes bibliographical references (leaves 155-162)
Keywords: Universiti Sultan Zainal Abidin -- Dissertations; Universiti Sultan Zainal Abidin -- Faculty of Medicine -- Dissertations; Blindness; Blindness -- Prevention; Blindness -- Malaysia -- Prevention; Cataract; Cataract -- Surgery; Cataract -- Surgery -- Complications; General Surgery; Dissertations, Academic